A metallic strain gauge–based experimental study of an analytic method for detection of urinary bladder dysfunction. (20th January 2015) - Das, Anupam; Deb, Anudyoti; Basak, Tapas Kumar; Saha, Arindita
Urinary bladder dysfunction is a major problem, affecting millions worldwide and causing major devastating medical conditions. The urinary bladder dysfunction not only leads to loss of control over the bladder muscles, but also affects the kidney and its functioning. This paper deals with an experimental approach towards the use of metallic strain gauge that produces an appreciable change in resistance with change in volume of urine in the bladder which can be used to study the dysfunction.